2019
DOI: 10.1029/2019tc005488
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene‐Holocene Slip Rate Along the Hasi Shan Restraining Bend of the Haiyuan Fault: Implication for Faulting Dynamics of a Complex Fault System

Abstract: The Haiyuan fault is a major left-lateral strike-slip fault at the boundary between northeast Tibet and the Gobi platform. Combining measurements of offset alluvial terraces with 10 Be-26 Al cosmogenic radionuclides dating, we bracket the late Quaternary slip rate along the Hasi Shan fault section (37°00′N, 104°25′E) of the Haiyuan fault. At our reference site, terrace-riser offsets for five successive terraces range from~5 to~200 m, and associated cosmogenic radionuclide ages range from 9 ± 3 to 44 ± 7 kyr. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 82 publications
(140 reference statements)
4
34
0
Order By: Relevance
“…To the east, westward changes in dextral rates southeast of the Qilian pushup remain uncertain. This is because the Gulang fault branches off the Lenglongling and Haiyuan Faults (e.g., Lasserre et al, 1999Lasserre et al, , 2002, while the latter includes parallel segments (e.g., Deng et al, 1986;Gaudemer et al, 1995;Li et al, 2017;Liu-Zeng et al, 2015;Matrau et al, 2019), and active strands of the former west of Menyuan are still poorly documented. Nevertheless, the fact that the large, parallel thrusts that underlie the Qilian Shan, Daxue Shan, Shulenan Shan, Danghenan Shan, and Tergun Daba Shan, contribute to transfer strike-slip rates from the Altyn Tagh to the Haiyuan Faults is beyond doubt (e.g., Daout et al, 2016;Gaudemer et al, 1995;Hetzel et al, 2004;Liu et al, 2021;Métivier et al, 1998;Meyer et al, 1998;Tapponnier et al, 1990;Xiong et al, 2017;Xu et al, 2010;Xu et al, 2021;Zheng, Zhang, He, et al, 2013) (Figure 22).…”
Section: The Fodongmiao Frontal Thrust Within Large Scale Block Kinematics Across Tibet's Northeast Boundarymentioning
confidence: 99%
“…To the east, westward changes in dextral rates southeast of the Qilian pushup remain uncertain. This is because the Gulang fault branches off the Lenglongling and Haiyuan Faults (e.g., Lasserre et al, 1999Lasserre et al, , 2002, while the latter includes parallel segments (e.g., Deng et al, 1986;Gaudemer et al, 1995;Li et al, 2017;Liu-Zeng et al, 2015;Matrau et al, 2019), and active strands of the former west of Menyuan are still poorly documented. Nevertheless, the fact that the large, parallel thrusts that underlie the Qilian Shan, Daxue Shan, Shulenan Shan, Danghenan Shan, and Tergun Daba Shan, contribute to transfer strike-slip rates from the Altyn Tagh to the Haiyuan Faults is beyond doubt (e.g., Daout et al, 2016;Gaudemer et al, 1995;Hetzel et al, 2004;Liu et al, 2021;Métivier et al, 1998;Meyer et al, 1998;Tapponnier et al, 1990;Xiong et al, 2017;Xu et al, 2010;Xu et al, 2021;Zheng, Zhang, He, et al, 2013) (Figure 22).…”
Section: The Fodongmiao Frontal Thrust Within Large Scale Block Kinematics Across Tibet's Northeast Boundarymentioning
confidence: 99%
“…Combining 10 Be CRN ages from surface and subsurface depth profiles in a set of terraces, Matrau et al (2019) constrained a minimum slip rate of 3.2 ± 0.2 mm/yr along one of the fault strands crossing the Hasi Shan restraining bend, within the western section of the 1920 Haiyuan earthquake rupture.…”
Section: Geologic Settingmentioning
confidence: 99%
“…However, higher slip rates have been documented (Zhang et al, 1988a;Gaudemer et al, 1995;Lasserre et al, 1999Lasserre et al, , 2002, as well as lower ones (Yuan et al, 1998;Li et al, 2009;He et al, 2010;Jiang et al, 2017;Matrau et al, 2019). Because it has been suggested that the fault slip rate might vary over time, thus, it is valuable to find multiple slip-rate constraints at a single site to constrain possible temporal slip-rate variation (e.g., Sieh and Jahns, 1984;Van der Woerd et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…According to the combined results, the Lenglong Ling Fault (F9), one of the most important parts of the Qilian-Haiyuan Fault, plays an important role in not only shaping regional topography, but also accommodating the tectonic deformation of the Tibetan Plateau relative to the Gobi-Ala Shan (Guo et al, 2017;Guo, Han, Mao, et al, 2019;Jiang et al, 2017). The renewed relative slow strike-slip rate (6.6 ± 0.3 mm/a) of the Lenglong Ling Fault (F9) (Guo et al, 2017), even the Qilian-Haiyuan Fault (Matrau et al, 2019;Yao et al, 2019), is much smaller than the slip rates of the Altyn Tagh Fault ( 10 mm/a) (Zhang, Molnar, & Xu, 2007) and the east Kunlun Fault ( 10 mm/a) (Kirby et al, 2007). Therefore, tectonic deformation transferred from the Altyn Tagh Fault and the east Kunlun Fault cannot be completely accommodated by the sinistral Lenglong Ling Fault (F9) (Duvall & Clark, 2010;Loveless & Meade, 2011).…”
Section: Discussionmentioning
confidence: 99%